CAUSES OF THE TECHNICAL PROFESSIONALS LACK IN THE CZECH REPUBLIC AND ITS ANALYSIS - VANĚK, Vladimír; VAŇKOVÁ, Hana (Trends in education, 2012)
The paper deals with the critical lack of technical professionals at the job market. It brings impulses for the improvement of current state in the Czech Republic on the base of programme analysis of primary and professional education and their comparison with trends in EU.
Keywords: general technical and professional education; framework educational programmes; European structural funds and integration processes; job market demands; social partnership; dual system of education; professional orientation; practical knowledge; preprofessional preparation; creative material.